Energy, exergy and exergoeconomic analysis of a cogeneration system for power and hydrogen production purpose based on TRR method and using low grade geothermal source. (January 2018) - Ghaebi, Hadi; Farhang, Behzad; Parikhani, Towhid; Rostamzadeh, Hadi
Highlights: Geothermal energy is used as a energy source for cogeneration of power and hydrogen. A modified ORC integrated with a PEM electrolyzer is used for power and hydrogen production. A comprehensive thermodynamic modelling of the integrated system is carried out. A comprehensive exergoeconomic analysis(based on TRR method) is performed. Abstract: In this research, a modified organic Rankine cycle (ORC) with a regeneration is used to generate power along with hydrogen. For hydrogen production purpose, a proton exchange membrane (PEM) electrolyzer is used, taking its required heating and power from the ORC. The proposed system is driven by geothermal energy. A comprehensive thermodynamic modelling (energy and exergy analysis) and exergoeconomic analysis are carried out for the proposed cycle, using various working fluids (i.e., R245fa, R114, R600 and R236fa) in order to compare their influences on performance of the integrated system. For this purpose, Engineering Equation Solver (EES) software is used in all conducted simulations which is proven to be the most professional and commercial software in thermodynamics. In addition, a comprehensive parametric study is carried out for investigating the effects of main thermodynamic flow parameters on the energetic, exergetic and economic factors of the integrated system. The results showed that R245fa had the highest energy and exergy efficiencies of 3.511% and 67.58%, respectively. Furthermore, it is the most cost-efficient working fluid with 11.54 $/GJ and 4.921 $/GJ average costs per exergy unit for output power and hydrogen production, respectively. Regarding their operational features and cost effectiveness, the working fluids R114, R600 and R236fa ranked successively after R245fa. Also R245fa had the lowest cost associated with the exergy destruction. Moreover, the results of parametric study showed that increasing of the evaporator pressure results in increasing of the output power, hydrogen production, and energy and exergy efficiencies, whereas the costs of output power and hydrogen production decreased. In addition, increasing the geothermal fluid temperature increases the output power, hydrogen production, and also their costs, while decreases the energy and exergy efficiencies. It is also found that an increase in the turbine extracted steam pressure (mean pressure) will increase the exergy efficiency, costs of produced power and hydrogen, whereas decrease the output power, hydrogen production, and energy efficiency.